(untitled) - Rhee, Man Young (Singapore, 2009)
Mobile Communication Systems and Security arms readers with a thorough understanding of all major cellular air-interface technologies and their security layer techniques. Rhee covers the technological development of wireless mobile communications in compliance with each iterative generation up to 3G systems and beyond, with an emphasis on wireless security aspects. By progressing in a systematic manner, presenting the theory and practice of wireless mobile technologies along with various security problems, readers will gain an intimate sense of how mobile systems operate and how to address complex security issues.
Keywords: Mobile communication systems,Wireless communication systems,Mobile communication systems,Wireless communication systems,Hệ thống viễn thông di động,Hệ thống viễn thông không dây,Hệ thống viễn thông di động,Hệ thống viễn thông không dây; Security measures,Security measures,Biện pháp an ninh,Biện pháp an ninh